Safety, tolerability, and pharmacokinetic evaluation of single‐ and multiple‐ascending doses of a novel kappa opioid receptor antagonist LY2456302 and drug interaction with ethanol in healthy subjects. (26th March 2014) - Lowe, Stephen L.; Wong, Conrad J.; Witcher, Jennifer; Gonzales, Celedon R.; Dickinson, Gemma L.; Bell, Robert L.; Rorick‐Kehn, Linda; Weller, MaryAnn; Stoltz, Randall R.; Royalty, Jane; Tauscher‐Wisniewski, Sitra
Abstract Accumulating evidence indicates that selective antagonism of kappa opioid receptors may provide therapeutic benefit in the treatment of major depressive disorder, anxiety disorders, and substance use disorders. LY2456302 is a high‐affinity, selective kappa opioid antagonist that demonstrates >30‐fold functional selectivity over mu and delta opioid receptors. The safety, tolerability, and pharmacokinetics (PK) of LY2456302 were investigated following single oral doses (2–60 mg), multiple oral doses (2, 10, and 35 mg), and when co‐administered with ethanol. Plasma concentrations of LY2456302 were measured by liquid chromatography‐tandem mass spectrometry method. Safety analyses were conducted on all enrolled subjects. LY2456302 doses were well‐tolerated with no clinically significant findings. No safety concerns were seen on co‐administration with ethanol. No evidence for an interaction between LY2456302 and ethanol on cognitive‐motor performance was detected. LY2456302 displayed rapid oral absorption and a terminal half‐life of approximately 30–40 hours. Plasma exposure of LY2456302 increased proportionally with increasing doses and reached steady state after 6–8 days of once‐daily dosing. Steady‐state PK of LY2456302 were not affected by coadministration of a single dose of ethanol. No clinically important changes in maximum concentration (Cmax) or AUC of ethanol (in the presence of LY2456302) were observed.